1975
DOI: 10.1139/v75-493
|View full text |Cite
|
Sign up to set email alerts
|

A Photoelectron Investigation of the Peroxide Bond

Abstract: R. S. BROWN. Can. J. Chem. 53,3439 (1975). The photoelectron spectra of several peroxides and their interpretation is presented. The effects of substituents is separated from vicinal orbital interactions using as a guideline the effect of similar substitution on the ether analogues. It is found that by comparison of Raman spectroscopic frequencies of the peroxide ground state, and vibrational frequencies for the ion (via pes), that the HOMO of peroxides is antibonding with respect to the 0-0 linkage. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…(iv) The top two E i s of MTP are mainly due to the lone pairs localized on the lactol pyran oxygen (O pyr ) and acetal oxygen (O Me ), respectively. Incidentally, it can be noted that the present OVGF results corroborate the semiempirical assignment proposed in earlier photoelectron studies on peroxides[71][72][73][74][75].…”
supporting
confidence: 91%
“…(iv) The top two E i s of MTP are mainly due to the lone pairs localized on the lactol pyran oxygen (O pyr ) and acetal oxygen (O Me ), respectively. Incidentally, it can be noted that the present OVGF results corroborate the semiempirical assignment proposed in earlier photoelectron studies on peroxides[71][72][73][74][75].…”
supporting
confidence: 91%
“…The low-lying a 1 A state of HO 2 + may play a significant role in the observed broadening. Their B3LYP calculations of the positions of the fundamental vibrations of ground-state HO 2 + yielded values which agreed well with the values (ν 1 = 3066.6, ν 2 = 1071.5, ν 3 = 1361.6 cm −1 ) subsequently obtained in the anharmonic MRCI calculations by Robbe and co-workers. 45 The multi-reference configuration interaction (MRCI) study also determined that the origin of theã 1 A state of HO 2 + should lie only about 1185 cm −1 above the ground-state origin.…”
Section: Most Of Our Understanding Of the Spectroscopic Properties Ofsupporting
confidence: 79%
“…Their observations determined that the first excited state of HOOH + lies approximately 16 800 cm −1 above the onset of ionization and its second excited state approximately 38 400 cm −1 above that onset. Later photoelectron studies by Brown 2 and by Ashmore and Burgess 3 confirmed those values and yielded an adiabatic ionization energy of 10.62 eV for the uncharged molecule. More recently, photoionization measurements by Litorja and Ruscic 4 refined the value for the first ionization energy of HOOH to 10.631(7) eV.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…P. Schaap, acetone (27) and cyclohexanone (28) diperoxides were prepared as described, tetramethoxyethylene was oxygenated (3) to prepare the dioxetane, the other dioxetanes were available from previous studies (23,25) and the other peroxides were prepared by Prof. R. S. Brown (29).…”
Section: Methodsmentioning
confidence: 99%